Fatigue in Aviation: Safety Risks, Preventive Strategies and Pharmacological Interventions - Wingelaar-Jagt, Yara Q.; Wingelaar, Thijs T.; Riedel, Wim J.; Ramaekers, Johannes G. (Frontiers in Physiology, 2021)
Fatigue poses an important safety risk to civil and military aviation. In addition to decreasing performance in-flight, (chronic) fatigue has negative long-term health effects. Possible causes of fatigue include sleep loss, extended time awake, circadian phase irregularities and work load. Despite regulations limiting flight time and enabling optimal rostering, fatigue cannot be prevented completely. Especially in military operations, where limits may be extended due to operational necessities, it is impossible to rely solely on regulations to prevent fatigue. Fatigue management, consisting of preventive strategies and operational countermeasures, such as pre-flight naps and pharmaceuticals that either promote adequate sleep (hypnotics or chronobiotics) or enhance performance (stimulants), may be required to mitigate fatigue in challenging (military) aviation operations. This review describes the pathophysiology, epidemiology and effects of fatigue and its impact on aviation, as well as several aspects of fatigue management and recommendations for future research in this field.